Strategies for diagnosing leg oedema in primary care: A qualitative study of GPs' approaches. (December 2014) - Diederich, Judith; Hartel, Simone; Baum, Erika; Bösner, Stefan
Abstract Background: The symptom leg oedema represents a broad range of possible underlying aetiologies. The background of leg oedema is multifactorial and usually the GP is the first contact point for patients presenting with this symptom. GPs rely on patient history and physical examination as their main diagnostic tools. Objective: To identify GPs' diagnostic approaches and heuristics in patients presenting with leg oedema. Methods: Interviews with 15 GPs (20–30 min) using a semi-structured interview-guideline were conducted. GPs described their individual diagnostic strategies concerning all patients presenting with leg oedema they had prospectively identified during the previous four weeks. Interviews were taped and transcribed verbatim. Qualitative analysis was conducted by two independent raters. Results: GPs applied a variety of diagnostic approaches, which can be grouped in active and passive strategies. Active strategies comprised the use of decision rules and guidelines, Bayesian arguing, problem dichotomisation and discrepancy heuristics. Passive approaches included test of time, therapy as diagnosis, and taking patient assumptions into account. Conclusion: When dealing with leg oedema, GPs use prior information of individual patients in a specific way. There is a broad variety of diagnostic approaches that can be grouped in 'active' and 'passive' behaviour. Approaches mostly match with established diagnostic strategies in primary care.